Comparing Effects of Reward Anticipation on Working Memory in Younger and Older Adults - Thurm, Franka; Zink, Nicolas; Li, Shu-Chen (Frontiers in Psychology, 2018)
Goal-directed behavior requires sufficient resource allocation of cognitive control processes, such as the ability to prioritize relevant over less relevant information in working memory. Findings from animal neural recording and human multimodal imaging studies suggest that dopamine-modulated reward incentive mechanisms could facilitate the encoding and updating of context representations, which can have beneficial effects on working memory performance in young age. In order to investigate whether these performance enhancing effects of reward on working memory processes are still preserved in old age, the current study aimed to investigate whether aging alters the effects of reward anticipation on the encoding and updating mechanisms in working memory processing. Therefore, a reward modulated verbal n-back task with age-adjusted memory load manipulation was developed to investigate reward modulation of working memory in younger (age 20–27) and older (age 65–78) adults. Our results suggest that the mechanism of reward anticipation in enhancing the encoding and updating of stimulus representations in working memory is still preserved in old age. EZ-diffusion modelling showed age distinct patterns of reward modulation on working memory processes. Whereas processes of memory evidence accumulation and sensorimotor speed benefited from reward modulation, responses did not become more cautious with incentive motivation for older adults as compared to younger adults. Furthermore, individual differences in reward-related enhancement of decision speed correlated with cognitive processing fluctuation and memory storage capacity in younger adults, but no such relations were observed in older adults. These findings indicate that although beneficial effects of reward modulation on working memory performance can still be observed in old age, not all working memory processes are facilitated when older adults are provided with reward incentives. Future research is needed to elucidate potential mechanisms of motivational incentive-related working memory plasticity in old age.